Pre-Hospital Spinal Immobilization: Neurological Outcomes for Spinal Motion Restriction vs. Spinal Immobilization - Nilhas, Aaron; Helmer, Stephen; Drake, Rachel; Reyes, Jared; Morriss, Megan; Haan, James M (Kansas Journal of Medicine, 2022)
Introduction. New recommendations for emergency medical services spinal precautions limit long spinal board use to extrication purposes only and are to be removed immediately. Outcomes for spinal motion restriction versus spinal immobilization were studied. Methods. A retrospective chart review of trauma patients was conducted over a 6-month period at a level I trauma center. Injury severity details and neurologic assessments were collected on 277 patients. Results. Upon arrival, 25 (9.0%) patients had a spine board in place. Patients placed on spine boards were more likely to be moderately or severely injured (ISS>15: 36.0% vs. 9.9%, p = 0.001) and more likely to have neurological deficits documented by EMS (30.4% vs. 8.8%, p = 0.01) and the trauma team (29.2% vs. 10.9%, p = 0.02). Conclusions. This study suggests that the long spine board is being properly used for more critically injured patients. Further research is needed to compare neurological outcomes using a larger sample size and more consistent documentation.